The perception and experience of infertile women who received acupressure in relation to anxiety: A qualitative study - Maryam Hassanzadeh-Bashtian; Talat Khadivzadeh; Shapour Badiee-Aval; Habibollah Esmaily (Iranian Journal of Nursing and Midwifery Research, 2018)
Background: Women, who are in a critical situation like infertility, are more prone to depression, anxiety, and low self-esteem than other people. The aim of this study was to explore the deep experience of anxiety in infertile women who received acupressure during in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). Materials and Methods: This qualitative, conventional content analysis study was performed on 14 infertile female participants in the Milad IVF Center in Mashhad, Iran, from September 2015 to August 2016. The study subjects included Iranian women, aged 20–45 (mean [standard deviation, SD] 29.07 [4.06]) years with primary infertility. Acupressure was performed on the Heart 7 and Pericardium 6 acupoints in 12 sessions. Data were gathered through semi-structured interviews, and transcribed, coded, and organized in different categories based on three primary phases of preparation, organization, and reporting. Results: The results showed the two major categories of “body perceptions of anxiety diminution” and “mind experiences.” The body perceptions category consisted of three subcategories, namely, reduction of nervous, cardiovascular, and gastrointestinal signs and symptoms. The subcategories of the mind experiences category consisted of emotional and cognitive consequences. Conclusions: The qualitative findings showed a number of positive outcomes in the physical and mental signs and symptoms of anxiety in infertile women undergoing IVF/ICSI, so acupressure can be used for reducing the unpleasant feelings and body perceptions of these women.